Characteristics of Host Rocks Manganese of The Anabanua Village Barru District South Sulawesi Province, Indonesia - Hasbi Bakri; Nurliah Jafar; Jamil Jumadra; Firman Nullah Yusuf; F., Firdaus (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
One of the prospects for a wealth of geological resources that can be utilized for the benefit of mankind is manganese metal mineral resources. In Anabanua Village, especially at the research location, there is an indication of manganese mineralization that the type of rock carrying the mineralization is not yet known. The purpose of this study was to determine the chemical elements of metallic minerals, mineralogy, and types of mineralization-carrying rocks, as many as three samples in the form of chunks, which were analyzed using megascopic analysis methods identifying the texture and structure of carrier rocks, XRD (X-Ray Diffraction) analysis minerals, and XRF (X-Ray Fluorescence). The characteristics of manganese mineralization carrier rocks consist of metallic elements Mn (0.046%-20.455%), Fe (1.555%-3.673%), and nonmetallic elements SiO2 (11.403%-48.165%), K2O (0.398%-4.177%). Mineralogy of manganese mineralization carrier rocks are roeblingite (Pb2Ca6Mn2+(Si3O9)2(SO4)2(OH)2·4H2O), rhodonite (CaMn3Mn[Si5O15]), diopside (CaMgSi2O6), calcite (CaCO3), kieserite (Al, Ga)2(GeO4)(OH)2), zeolite (Mn2O.Al2O3.xSiO .yH2O), and palygorskite ((Mg, Al)2 Si4O 10(OH)·4H2O). Manganese mineralization host rocks are determined by referring to the SiO2 (%weight) and K2O(%weight) diagrams to produce basalt igneous rock types.